MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN PESANTREN (STUDI KASUS DI YAYASAN ROUDLOTUS SHOLIHIN GUNUNG TERANG, LAMPUNG) - Khalimi Dzakwan; Diana Lutfiani Putri (Jurnal Riset Multidisiplin Edukasi, 2026)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia, serving as centers of learning and dormitories for students under the guidance of kyai and ustadz to comprehensively study religious knowledge and develop holistic character. Pesantren now need professional HRM to improve the quality of ustadz, curriculum effectiveness, and competitive education quality, although its implementation is often not optimal, such as a lack of recruitment and training planning. This study describes HRM practices at the Roudlotus Sholihin Gunung Terang Foundation in Lampung, including planning, recruitment, training, evaluation, and facilities, in order to provide recommendations for improving the quality of education. Qualitative research on HRM to improve the quality of education at the Roudlotus Sholihin Gunung Terang Islamic Boarding School in Lampung collected descriptive data through in-depth interviews with the head of the curriculum, teachers, and students; direct observation; and supporting documents such as the boarding school profile, which were analyzed descriptively through reduction, presentation, and conclusion drawing to provide practical understanding and relevant recommendations for boarding school administrators. Planning, needs analysis, rigorous recruitment, and human resource competency development at the Roudlotus Sholihin Gunung Terang Foundation in Lampung have proven to be effective strategic pillars that optimize the performance of teachers and staff to improve the quality of Islamic boarding school education holistically. The implications of HRM include performance improvement through regular assessments, motivation via incentives, curriculum and teaching method innovation, disciplined student management, and optimization of facilities and infrastructure, all of which support operational effectiveness and the development of competitive students. Despite facing operational limitations, the pesantren has succeeded in turning challenges into opportunities through internal-external synergy and gap mapping for modern infrastructure development. This study provides practical recommendations for pesantren administrators on data-based HRM, contributing to competitive Islamic education and national policies such as the Pesantren Unggulan (Leading Pesantren) program.